Counterterrorism Policies in Sub-Saharan Africa - Ename Minko, Abraham (Advanced Studies on Socio-Economy Development, 2024)
In response to the escalating threat of terrorism, counterterrorism policies have been globally implemented. This social and political landscape has raised significant concerns about the impact on human rights fulfillment, particularly in Sub-Saharan Africa. To elaborate on this problem, this article critically examines the effects of these policies on human rights within the region, mainly by analyzing the legal and institutional frameworks that underpin counterterrorism strategies in various Sub-Saharan countries. Utilizing a qualitative research design, this study employs content analysis of legal documents, policy reports, and other relevant texts to explore the interplay between counterterrorism efforts and the protection of human rights. The study specifically evaluates the impact of these policies on civil and political rights, economic, social, and cultural rights, as well as the right to privacy. It also addresses states' challenges in balancing social security needs with protecting human rights. The paper argues that while counterterrorism is necessary, it must be implemented in a manner that respects human rights and the rule of law. Therefore, the paper recommends that states adopt a human rights-centered approach as a counterterrorism strategy, ensuring that legal and institutional frameworks align with international human rights standards. This approach offers a hopeful path forward, promising both effective counterterrorism and the protection of human rights. Keywords: Counterterrorism, human rights, Policies, Sub-Saharan Africa